Analisis Perlindungan Hukum Terhadap Konsumen dalam Transaksi Pembiayaan Hunian Akad Iṣtiṣna’ dan Murābahah : Studi di Perumahan Graha Tata Persada Gowa - Dewi Arviani Pasimai; Marilang; Rahman Ambo Masse (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe and analyze housing financing transactions based on sharia contracts, the form of legal protection provided to consumers by the developer in the Graha Tata Persada Gowa housing complex, and the factors influencing the implementation of housing financing transactions from the perspective of Islamic law. The study employs a qualitative method with a sharia-based approach and a phenomenological approach. Data were collected through observation, interviews, and documentation, using both primary and secondary data sources. The findings show that, based on the transaction mechanism and the financing process applied, housing transactions at Graha Tata Persada Gowa have been carried out in accordance with sharia principles, reflecting the application of the istisna’ contract in the procurement and construction of housing. Furthermore, in terms of home ownership financing, the mechanism used indicates a clear sale-and-purchase transaction between the bank, the developer, and the consumer, with the price and payment obligations agreed upon in advance. This is consistent with the principles of the murabahah contract. However, the implementation of consumer protection in housing financing transactions has not fully met the principles of justice and the fulfillment of consumer rights under Islamic law. The researcher proposes four stages of a mechanism that is in line with Islamic law, namely: identification and determination of defects (‘aib), affirmation of the developer’s responsibility (mas’uliyyah), granting the consumer the right of choice, and resolution through deliberation (musyawarah).